Bilateral Facial Palsy in Rapidly Progressive Course of Wegener's Granulomatosis: A Case Report. (25th September 2013) - Roszkowska, Anna; Morawska-Kochman, Monika; Temporale, Hanna; Sikorska-Żuk, Małgorzata; Kręcicki, Tomasz
Abstract : Introduction . Wegener's granulomatosis belongs to a group of systemic vasculitis diseases, which is characterized by necrotizing vasculitis and presence of granulomas. In a lot of cases, the first symptoms of the disease are observed in the head and neck region, but the bilateral facial nerve palsy occurs very rarely. Objective . The objective of our report was to describe the unusual course of Wegener's granulomatosis with the bilateral facial nerve paralysis, which subsided after application of steroids and immunosuppressive therapy in combination with surgical treatment. Results and Conclusions . Hearing loss may precede other symptoms in Wegener's granulomatosis. Ear pain and otorrhea may suggest the diagnosis of bacterial purulent otitis media and delay the proper diagnosis. In the presented case, considering the clinical course, it was necessary to apply both pharmacological and surgical treatments.